1992
DOI: 10.1007/bf02784618
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and copper in the serum of diabetic patients

Abstract: The Zn/Cu ratio was examined in the serum of three groups of persons: healthy volunteers, diabetic patients on diabetic diet (NIDDM), and diabetic patients on diabetic diet and insulin (IDDM). Zinc, copper, the Zn/Cu serum ratio, and the blood glucose level were determined during fasting and 2 h after breakfast. Zn and Cu serum levels in NIDDM and IDDM patients were decreased. The Zn/Cu ratio was higher in both groups of diabetic patients. These changes in the Zn and Cu levels as well as in the Zn/Cu ratio wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 10 publications
2
9
1
2
Order By: Relevance
“…Serum magnesium concentration has been reported to decrease in diabetics [8,9]; furthermore, increased renal loss of chromium and selenium [10,11] and also hyperzincuria have been observed [12,13]. Similar results have been published by Hungarian authors [11,14].…”
Section: Introductionsupporting
confidence: 78%
“…Serum magnesium concentration has been reported to decrease in diabetics [8,9]; furthermore, increased renal loss of chromium and selenium [10,11] and also hyperzincuria have been observed [12,13]. Similar results have been published by Hungarian authors [11,14].…”
Section: Introductionsupporting
confidence: 78%
“…The Zn/Cu ratio was chosen as an index of distribution of trace elements, because this ratio was previously shown to correlate with carcinogenicity and altered immune function [48][49][50][51]. Notably, changes in Zn/Cu ratio in the present study were still tissue-specific; high-dose pDCB led to a marked Zn/Cu ratio increase in the liver and a trend towards a decrease in blood, whereas the Zn/Cu ratio changes in the kidney were statistically insignificant.…”
Section: Discussioncontrasting
confidence: 58%
“…To characterize the effects of pDCB on Zn and Cu homeostasis, the ratio of tissue Zn to Cu was calculated [48][49][50][51], as shown in Fig. 8.…”
Section: Effects Of Pdcb On the Ratio Zn To Cu In The Liver And Kidneymentioning
confidence: 99%
“…Except for higher levels of serum Cu observed in subjects with DN, we did not find any significant difference for either serum or urinary Cu among uncomplicated T2D patients or T2D patients with either DR or DPN. An earlier study reported no significant differences for either Zn or Cu levels, as well as the Zn/Cu ratio in diabetic patients with and without complications [34]. Another cross-sectional study that evaluated 24 h urinary Cu levels in T2D patients ( n = 42) with DN in comparison with patients without DN ( n = 40) reported that diabetic patients with DN have increased urinary Cu excretion [31].…”
Section: Discussionmentioning
confidence: 99%